Energy income and farm viability: Evidence from USDA farm survey data - Grout, Travis; Ifft, Jennifer; Malinovskaya, Anna (Energy policy, 2021)
There are frequent and increasing conflicts between energy development and agricultural land use. In these debates, claims are commonly made that energy income can improve farm viability. We develop a conceptual model that provides a framework for when and how energy income could improve farm viability. If farms face difficulty accessing credit, they invest at below optimal levels. In such cases, energy income may be used to increase investment, thus strengthening the farm economy. We test the predictions of this model with detailed, nationally representative U.S. Department of Agriculture farm survey data. This large, cross sectional dataset is well suited to propensity score matching and allows us to test whether observationally similar farms with and without energy income have different levels of credit access and capital investment. We are able to test whether model outcomes are similar under different farm and energy income definitions. Overall, we find little evidence that energy income improves credit access or increases capital investments. This suggests that on average the benefits of energy income for farm household consumption do not necessarily extend to the farm economy or agricultural production. •Energy income received by farms might be consumed or invested.•If farms already have access to credit, energy income will not affect investment.•A large 2014 U.S. farm survey dataset is used to analyze impacts of energy income.•Energy income is not related to credit access or investment by U.S. farms.